2016
DOI: 10.1016/j.tranpol.2015.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the attractiveness of a new light rail extension: Testing simple change and displacement change hypotheses

Abstract: Many communities in the United States have been adding new light rail to bus-predominant public transit systems. However, there is disagreement as to whether opening light rail lines attracts new ridership or merely draws ridership from existing transit users. We study a new light rail line in Salt Lake City, Utah, USA, which is part of a complete street redevelopment. We utilize a pre-test post-test control group quasi-experimental design to test two different measures of ridership change. The first measure i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Although street renovations are sometimes related to more self-reported walking (Pazin et al, 2016) or accelerometer-measured walking (Brown et al, 2016), other studies show no increased use after street renovations (Boarnet et al, 2013) or greenway construction (West and Shores, 2011, 2015). Past evaluations of the complete street reported in the current study showed more nearby residents used complete street transit than before (Brown et al, 2015), and more people were counted at transit stops than before (Werner et al, 2016). Some research has related more pedestrian counts in New York City to walkable features on the block such as street furniture and multiple windows facing the street (Ewing et al, 2016); however, other research in a Midwest city has shown higher pedestrian counts related to less walkable features, such as graffiti and litter (Suminski et al, 2008).…”
Section: Introductionmentioning
confidence: 57%
“…Although street renovations are sometimes related to more self-reported walking (Pazin et al, 2016) or accelerometer-measured walking (Brown et al, 2016), other studies show no increased use after street renovations (Boarnet et al, 2013) or greenway construction (West and Shores, 2011, 2015). Past evaluations of the complete street reported in the current study showed more nearby residents used complete street transit than before (Brown et al, 2015), and more people were counted at transit stops than before (Werner et al, 2016). Some research has related more pedestrian counts in New York City to walkable features on the block such as street furniture and multiple windows facing the street (Ewing et al, 2016); however, other research in a Midwest city has shown higher pedestrian counts related to less walkable features, such as graffiti and litter (Suminski et al, 2008).…”
Section: Introductionmentioning
confidence: 57%
“…Prior evaluations of new LRT have recruited people into treatment (exposed) and control groups based on distance from their homes to new rail stations [59][60][61][62][63][64][65][66]. There is debate on the degree to which LRT investments induce new transit ridership versus shifting existing users from bus to rail [57,[71][72][73]. The current study attempts to overcome this limitation by focusing recruitment on university staff who both live and work near the rail line.…”
Section: Study Sample and Eligibilitymentioning
confidence: 99%
“…walking and cycling, and their combination with public transport use) is key to overcoming multiple urban health and environmental challenges such as congestion, traffic injuries, air pollution, greenhouse emissions, and noise (Brand and Preston, 2010; European Environment Agency (EEA), 2018; European Environment Agency (EEA) and European Topic Centre on Air Pollution and Climate Change Mitigation (ETC/ACM), 2018; Guthold et al, 2018;Taipale and Fellini, 2012;The Shift Project, 2019;The World Bank, 2012;United Nations, 2017). People who engage in public transport have also been shown to report higher levels of walking than others (Besser and Dannenberg, 2005;Gascon et al, 2019;Lachapelle and Noland, 2012;Langlois et al, 2016;Morency et al, 2011;Rissel et al, 2012;Sener et al, 2016), and access to public transport was shown to increase levels of walking in natural experiment studies (Brown et al, 2015;Miller et al, 2015;Werner et al, 2016). Thus, beyond sustainability issues, promoting public transport can also help urban population reach the much needed recommended levels of physical activity (WHO, 2018).…”
Section: Introductionmentioning
confidence: 99%